GapB Is Involved in Biofilm Formation Dependent on LrgAB but Not the SinI/R System in Bacillus cereus 0-9 - Zhang, Juanmei; Meng, Li; Zhang, Yubing; Sang, Lidan; Liu, Qing; Zhao, Linlin; Liu, Fengying; Wang, Gang (Frontiers in Microbiology, 2020)
Bacillus cereus 0-9, a gram-positive endospore-forming bacterium isolated from healthy wheat roots, has biological control capacity against several soil-borne plant diseases of wheat such as sharp eyespot and take-all. The bacterium can produce various biofilms that differ in their architecture and formation mechanisms, possibly for adapting to different environments. The gapB gene, encoding a glyceraldehyde-3-phosphate dehydrogenase (GAPDH), plays a key role in B. cereus 0-9 biofilm formation. We studied the function of GapB and the mechanism of its involvement in regulating B. cereus 0-9 biofilm formation. GapB has GAPDH activities for both NAD+- and NADP+-dependent dehydrogenases and is a key enzyme in gluconeogenesis. Biofilm yield of the ΔgapB strain decreased by 78.5% compared with that of wild-type B. cereus 0-9 in Lysogeny broth supplemented with some mineral salts (LBS), and the ΔgapB::gapB mutants were recovered with gapB gene supplementation. Interestingly, supplementing the LBS medium with 0.1%–0.5% glycerol restored the biofilm formation capacity of the ΔgapB mutants. Therefore, GapB regulates biofilm formation relative to its function in gluconeogenesis. To illustrate how GapB is involved in regulating biofilm formation through gluconeogenesis, we carried out further research. The results indicate that GapB regulated the B. cereus 0-9 biofilm formation independently of the exopolysaccharides and regulatory proteins in the typical SinI/R system, likely owing to the release of extracellular DNA in the matrix. Transcriptome analysis showed that gapB deletion caused changes in the expression levels of only 18 genes, among which, lrgAB was the most significantly increased by 6.17-fold. We confirmed this hypothesis by counting the dead and living cells in the biofilm, and found the number of living cells in the biofilm formed by the ΔgapB strain was nearly 7.5 times than that of wild-type B. cereus 0-9. Therefore, we concluded that GapB is involved in extracellular DNA release and biofilm formation by regulating the expression or activities of LrgAB. These results provide new insight into the regulatory mechanism of bacterial biofilm formation and a new foundation for further studying the stress resistance of B. cereus.